Pleistocene Walrus (Odobenus Rosmarus) from Forteau, Labrador - Harington, Charles; Anderson, Thane; Rodrigues, Cyril (Géographie physique et Quaternaire, 1993)
ABSTRACTA partial skeleton of an adult male walrus (Odobenus rosmarus) was excavated from a raised beach on the Labrador coast, near the present community of Forteau. Bone collagen from the specimen has been radiocarbon dated at about 11 500 yr BP. Fossil pollen, dinoflagellates, diatoms, sponges, echinoderms, barnacles, foraminifers and ostracodes from sandy clay surrounding the specimen are considered in terms of their paleoenvironmental implications. Presuming the bone date is correct, palynological and molluscan data suggest that the walrus skeleton was reworked and redeposited by a receding sea some 10 300 to 10 400 years ago, when sparse tundra vegetation evidently bordered on a glaciomarine environment.